2021
DOI: 10.3390/ijerph182010999
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 among Healthcare Workers: A Prospective Serological-Epidemiological Cohort Study in a Standard Care Hospital in Rural Germany

Abstract: Healthcare workers (HCW) play a vital role in the SARS-CoV-2 pandemic control. The aim of this study was to assess the prevalence of SARS-CoV-2 antibodies and the risk of COVID-19 infections in a cohort of HCW from four different risk groups (from intensive care unit to administration) of a hospital of a primary care level in rural Germany. The outcomes were monthly measures of antibody seroprevalence over a period of 6 months. Overall, a seroprevalence of 13.41% was determined, with significantly higher preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Though the cumulative incidence of SARS-CoV-2 was low in our study, and despite all the training efforts, HW with regular patient contact or who worked in an ICU had an increased infection risk. This is consistent with results from other studies which observed increased infection risks in HW [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 31 ]. Therefore, studies on continuous improvement of infection prevention and control for HW are needed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Though the cumulative incidence of SARS-CoV-2 was low in our study, and despite all the training efforts, HW with regular patient contact or who worked in an ICU had an increased infection risk. This is consistent with results from other studies which observed increased infection risks in HW [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 31 ]. Therefore, studies on continuous improvement of infection prevention and control for HW are needed.…”
Section: Discussionsupporting
confidence: 93%
“…In a six-month follow-up study during the summer of 2020—a period of low COVID-19 incidence in the general population of Germany—the rate of positive IgG in HW was 0.75% [ 30 ]. A similar study performed in another region of Germany that covered the period of six months from July to December 2020, thereby including the second wave of COVID-19, reported a seroprevalence of 13.4% [ 31 ]. The prevalence rate was significantly higher among HW working in worksites with more frequent contact with confirmed or suspected cases (30.3%, p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…Korth et al found a seroprevalence rate of 5.1% in 315 HCW between August and December 2020 at the University Hospital Essen, close to our region [21]. Another study in Oberspreewald-Lausitz reported a seroprevalence of 13.3% in 166 HCWs between July and December 2020 in a standard care hospital [35]. During the second and third observational period in our study, the incidence in the general population of the region of Recklinghausen and the number of COVID-19 patients increased markedly.…”
Section: Discussionmentioning
confidence: 53%
“…B. Ärzt*innen), allein durch die Unterstützung bei der Körperpflege näher und länger an Patient*innen und damit einem höheren eigenen Infektionsrisiko ausgesetzt. Eine Brandenburger Studie stellte gruppenspezifische Unterschiede innerhalb des Krankenhauspersonals hinsichtlich des Risikos einer Infektion mit Covid-19 dar und zeigte, dass medizinisches Personal mit häufiger Expo-sition ein erhöhtes Risiko zu haben scheint [11]. Auch schätzen Pflegekräfte ihren eigenen Gesundheitsstatus schlechter ein als andere Gesundheitsfachkräfte, beispielsweise Ärzt*innen [4,8].…”
Section: Psychosoziale Belastungunclassified